Co-digestion of terrestrial plant biomass with marine macro-algae for biogas production. (October 2016) - Akunna, J.C.; Hierholtzer, A.
Abstract: This paper investigates factors affecting anaerobic degradation of marine macro-algae (or seaweed), when used as a co-substrate with terrestrial plant biomass for the production of biogas. Using Laminaria digitata, a brown marine seaweed species and green peas, results showed that when only 2% of feedstock of a reactor treating the green peas at an organic loading rate (OLR) of 2.67 kg VS m 3 day −1 was replaced with the seaweed, methane production was disrupted, whilst acidogenesis, seemed to be less adversely affected, resulting in excessive volatile acids accumulation. Reactor stability was difficult to achieve thereafter. The experiment was repeated with a lower initial OLR of green peas of 0.70 kg VS m 3 day −1 before the addition of the seaweed. Although similar symptoms as in first trial were observed, process stability was restored through the control of OLR and alkalinity. These measures led to an increase in overall OLR of 1.25 kg VS m 3 day −1 comprising of 35% seaweed. This study has shown that certain seaweed constituents are more inhibitory to the methanogens even at trace concentrations than to the other anaerobic digestion microbial groups. Appropriate adaptation strategy, involving initial low proportion of the seaweed relative to the total OLR, and overall low OLR, is necessary to ensure effective adaptation of the microorganisms to the inhibitory constituents of seaweed. Where there is seasonal availability of seaweed, the results of this study suggest that a fresh adaptation or start-up strategy must be implemented during each cycle of seaweed availability in order to ensure sustainable process stability. Highlights: Certain constituents of seaweed exhibit antimicrobial effects even at trace concentrations. Methanogenesis is most sensitive step to the antimicrobial constituents. Co-digestion with seaweed requires relatively long start-up period. Viable co-digestion will depend on microbial responses to seaweed variability and availability.